1989
DOI: 10.1152/jn.1989.62.1.273
|View full text |Cite
|
Sign up to set email alerts
|

Mastication in the rabbit: a description of movement and muscle activity

Abstract: 1. Mastication was studied in awake rabbits that had previously been prepared for chronic recording of jaw movement and jaw muscle electromyography (EMG) under general anesthesia. Data were stored on tape and replayed for computer-assisted analysis. Most data was taken from the mastication of rabbit chow, but the basic features described in the paper also apply to eating of other foods. The series of movements was divided into cycles, and the phases that compose them, using peaks in the vertical movement, velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 0 publications
8
63
0
1
Order By: Relevance
“…Contraction of the suprahyoid muscles depresses the mandible when the hyoid bone is fixed or elevates the hyoid bone when the mandible is fixed. Depression of the mandible is associated with jaw opening that occurs during lapping, licking, chewing, and phonation (FaaborgAndersen and Venard, 1964;Moller, 1966;Crompton et al, 1975;Schwartz et al, 1989;Yamada et al, 1993). Displacement of the hyoid bone occurs during swallowing (Logemann, 1983) and breathing (Lowe and Sessle, 1973;Van de Graaff et al, 1984).…”
Section: Functions Of Mh Musclementioning
confidence: 99%
“…Contraction of the suprahyoid muscles depresses the mandible when the hyoid bone is fixed or elevates the hyoid bone when the mandible is fixed. Depression of the mandible is associated with jaw opening that occurs during lapping, licking, chewing, and phonation (FaaborgAndersen and Venard, 1964;Moller, 1966;Crompton et al, 1975;Schwartz et al, 1989;Yamada et al, 1993). Displacement of the hyoid bone occurs during swallowing (Logemann, 1983) and breathing (Lowe and Sessle, 1973;Van de Graaff et al, 1984).…”
Section: Functions Of Mh Musclementioning
confidence: 99%
“…By contrast, the durations of the closing phases did not correlate with T C . However, further work in rabbits demonstrated that correlations between phase durations and T C depended on cycle type, viz., Type I (preparatory series), II (reduction series), and III (pre-swallow series) (Schwartz et al, 1989). These investigators found positive correlations between opening phases and T C during Type I and III chews, but not during Type II chews.…”
Section: Phase Modulation and Chewing Series (Preparatory Reductionmentioning
confidence: 82%
“…Over the course of a chewing sequence, the functional nature of chewing shifts from ingestion and initial food handling in the front or anterior part of the mouth (preparatory series) to grinding and reducing the food in the molar region (reduction series) to introducing the food into the pharynx in preparation for swallowing (pre-swallow series). Chewing cycles tend to have the shortest durations during the preparatory series and the longest durations during the preswallow series as detailed in (Schwartz et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations